Microfilarae in malignant mesothelioma associated pleural effusion with blood microfilaremia: a rare association - Sharma, Dinesh Chandra; Sharma, Deepanjali (International Journal of Advances in Medicine, 2019)
Filariasis has a wide spectrum of presentation and usually involves the lung in the form of tropical pulmonary eosinophilia with pulmonary infiltrates and peripheral eosinophilia. Filariasis presenting with pleural effusion is an unusual presentation. Malignancy in association with filarial pleural effusion is extremely rare. In this context, we hereby report a case of 45 year old male who presented with right sided chest pain, cough, fever and generalized weakness. Pleural fluid cytology revealed microfilaria and pleural biopsies from pleural nodules confirmed malignant mesothelioma. Peripheral blood smears taken at night exhibited microfilaria with normal eosinophil counts, which is further uncommon. Role of filariasis in tumorigenesis is controversial.